Mechanistic basis for protection of differentiated SH-SY5Y cells by oryzanol-rich fraction against hydrogen peroxide-induced neurotoxicity - Ismail, Norsharina; Ismail, Maznah; Imam, Mustapha Umar; Azmi, Nur Hanisah; Fathy, Siti Farhana; Foo, Jhi Biau; Abu Bakar, Muhammad Firdaus (BioMed Central, 2014)
Background Apoptosis is often the end result of oxidative damage to neurons. Due to shared pathways between oxidative stress, apoptosis and antioxidant defence systems, an oxidative insult could end up causing cellular apoptosis or survival depending on the severity of the insult and cellular responses. Plant bioresources have received close attention in recent years for their potential role in regulating the pathways involved in apoptosis and oxidative stress in favour of cell survival. Rice bran is a bioactive-rich by-product of rice milling process. It possesses antioxidant properties, making it a promising source of antioxidants that could potentially prevent oxidative stress-induced neurodegenerative diseases. Methods Thus, the present study investigated the neuroprotective properties of oryzanol-rich fraction (ORF) against hydrogen peroxide (H2O2)-induced neurotoxicity in differentiated human neuroblastoma SH-SY5Y cells. ORF was extracted from rice bran using a green technology platform, supercritical fluid extraction system. Furthermore, its effects on cell viability, morphological changes, cell cycle, and apoptosis were evaluated. The underlying transcriptomic changes involved in regulation of oxidative stress, apoptosis and antioxidant defence systems were equally studied. Results ORF protected differentiated SH-SY5Y cells against H2O2-induced neurotoxicity through preserving the mitochondrial metabolic enzyme activities, thus reducing apoptosis. The mechanistic basis for the neuroprotective effects of ORF included upregulation of antioxidant genes (catalase, SOD 1 and SOD 2), downregulation of pro-apoptotic genes (JNK, TNF, ING3, BAK1, BAX, p21 and caspase-9), and upregulation of anti-apoptotic genes (ERK1/2, AKT1 and NF-Kβ). Conclusion These findings suggest ORF may be an effective antioxidant that could prevent oxidative stress-induced neurodegenerative disorders.